Self-measurement of blood pressure: strengths and limitations in clinical and research settings - E. V. Platonova; V. M. Gorbunov; S. A. Shalnova (Кардиоваскулярная терапия и профилактика)
The article describes in detail the evidence on validation and classification of existing devices for blood pressure self-control (BPSC). The strengths and limitations of BPSC are discussed, together with modern approaches to research and clinical application of BPSC as independent method or in combination with traditional BP measurement. The current clinical and epidemiologic evidence on BPSC is analysed. Technical and clinical aspects of the method in general and of tonometer use, in particular, are emphasised.